2013
DOI: 10.1073/pnas.1314242110
|View full text |Cite
|
Sign up to set email alerts
|

Axial interactions in the mixed-valent Cu A active site and role of the axial methionine in electron transfer

Abstract: Within Cu-containing electron transfer active sites, the role of the axial ligand in type 1 sites is well defined, yet its role in the binuclear mixed-valent Cu A sites is less clear. Recently, the mutation of the axial Met to Leu in a Cu A site engineered into azurin (Cu A Az) was found to have a limited effect on E 0 relative to this mutation in blue copper (BC). Detailed low-temperature absorption and magnetic circular dichroism, resonance Raman, and electron paramagnetic resonance studies on Cu A Az (WT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
38
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 43 publications
7
38
0
Order By: Relevance
“…axial position is consistent with previous reports of mutations at the other axial Met123 position 24,42 and leads us to conclude that the diamond core structure of Cu 2 S Cys2 shown in Figure 1B is resistant to variations of axial interactions.…”
Section: Hhmi Author Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…axial position is consistent with previous reports of mutations at the other axial Met123 position 24,42 and leads us to conclude that the diamond core structure of Cu 2 S Cys2 shown in Figure 1B is resistant to variations of axial interactions.…”
Section: Hhmi Author Manuscriptsupporting
confidence: 92%
“…Previous studies of Cu A azurin has shown that mutations of the axial Met to Glu, Gln or Leu resulted in only ∼ 20 mV changes of the reduction potentials of the Cu A azurin. 24 The lack of change in reduction potential observed for the amide to ester carbonyl change in another axial position is consistent with previous reports of mutations at the other axial Met123 position 24,42 and leads us to conclude that the diamond core structure of Cu 2 S Cys2 shown in Figure 1B is resistant to variations of axial interactions. In summary, a Cu A azurin variant consisting of an amide-to-ester replacement in the backbone has been prepared to investigate the properties of the carbonyl interaction with the Cu A center.…”
supporting
confidence: 91%
“…While functioning as an ET protein, the Fe–S(Met) bond keeps the metal low-spin while the heme iron site shuttles between Fe(II) and Fe(III), which maintains a low inner-sphere reorganization energy for rapid ET (3, 4, 6). However, cyt c can also function as a peroxidase, which requires loss of the Fe(III)–S(Met) bond to open a ligand binding site for catalysis (7, 8).…”
mentioning
confidence: 99%
“…Parallel studies were done on the binuclear Cu A center in Fig 1, which defined an equivalent role of the protein stabilized thioether-Cu bond: to stabilize the oxidized over the reduced state, and to tune down the Cu A reduction potential. [25] From Fig 1, cytochrome c has a thioether-metal bond that was thought to play the opposite role in function. This is considered in the next section.…”
Section: – Role Of the Protein In Active Site Geometric And Electromentioning
confidence: 99%